1998
DOI: 10.1207/s15374424jccp2703_8
|View full text |Cite
|
Sign up to set email alerts
|

Medical, cognitive, emotional, and behavioral outcomes in school-age children conceived by In-Vitro Fertilization

Abstract: Assessed long-term effects of assisted reproduction technologies of in-vitro fertilization (IVF) and related techniques of embryo transfer (ET) on children's adjustment. 51 school-age Israeli children conceived by IVF/ET were compared with 51 control-matched children conceived spontaneously. The assessment included a comprehensive medical evaluation, a psychological examination, teachers' reports, parents' reports, and children's self-reports. As compared with controls, IVF/ET children did not reveal significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 34 publications
4
41
1
4
Order By: Relevance
“…Our findings are reassuring and in line with the recent studies in young IVF children [2,4,7,8,10,11,14,[19][20][21][22][23][24][25] and at primary school age [12,17,18]. Olivennes et al [17] found, in a follow-up study of 422 IVF children aged 6 to 13 years, according to the French school system, that 92.2% of the children had at least average school achievement.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings are reassuring and in line with the recent studies in young IVF children [2,4,7,8,10,11,14,[19][20][21][22][23][24][25] and at primary school age [12,17,18]. Olivennes et al [17] found, in a follow-up study of 422 IVF children aged 6 to 13 years, according to the French school system, that 92.2% of the children had at least average school achievement.…”
Section: Discussionsupporting
confidence: 90%
“…In 1-to 9-year-old IVF children conceived from cryopreserved embryos, the same authors found comparable results for scholastic performance in the school-age children [18]. Levy-Shiff et al [12] examined 9-and 10-year-old IVF children in comparison with naturally conceived children recruited from the IVF children's schools and found that intelligence did not differ between the groups. In addition, our findings show also that the tendency of good educational outcome in IVF children continues at secondary school.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…There were no differences in child adjustment between the IVF and naturally conceived children as rated by parents or teachers. Only one study, conducted in Israel, reported raised levels of emotional problems among IVF children of middle-school age (Levy-Shiff et al, 1998). In comparison with naturally conceived children, IVF children showed poorer adjustment to school as rated by teachers, and reported themselves to be more aggressive, more anxious, and more depressed.…”
Section: Children In Ivf Familiesmentioning
confidence: 99%